AUTOIMPORT OF A LARGE VOLUME INFORMATION INTO A DATABASE USING THE PYTHON PROGRAMMING LANGUAGE - Krapivin, Roman R.; Filatov, Yuri M.; Gareeva, Gulnara A.; Faizullina, Aigul G.; Myshkina, Irina Yu (International journal of advanced studies, 2023)
The article discusses an efficient and automated way to import large amounts of data from Excel tables into a database. In various projects, there are tasks in which the flow of huge data, such as logs of program operations or manual operations performed at work sites, is vital for effective analysis. Purpose – development of a module for automatic import of a large amount of data from Excel format into a database. Method or methodology of work: the article discusses a method that implements automatic import of data from Excel tables into a Postgresql database. Result: developed its own unique module that is able to process huge Excel tables and import them into a Postgresql database without manual operations. Scope of the results: the data obtained, which are stored in the database, should be used to identify high-yield accounts for subsequent investment.